Analysis of Global Research on Malaria and Plasmodium vivax - Garrido-Cardenas, José Antonio (Int J Environ Res Public Health, 2019)
Background: Malaria is one of the infectious diseases of greatest interest to the scientific community and of greatest concern to international health authorities. Traditionally, the focus has been on Plasmodium falciparum, the parasite that causes the most severe form of the disease in Africa. However, in the last twenty years, the Plasmodium vivax parasite, responsible for a large number of cases in Latin America, the Middle East, South and Southeast Asia, the Horn of Africa, and Oceania, has also generated enormous interest due, among other things, to the published evidence that it can cause severe malaria. Methods: In this paper, the international scientific publication on malaria and P. vivax has been analyzed using the Scopus database to try to define global trends in this field of study. Results: It has been shown that events such as the emergence of resistance to certain drugs can break a trend. The important role of non-malaria-endemic countries such as the USA or Switzerland in malaria research is also evident. Conclusions: International cooperation will be essential for the eradication of the disease. Moreover, in this sense, the general vision given by the bibliometric analysis of malaria caused by P. vivax is fundamental to paint the picture regarding the current situation and encourage international cooperation and control efforts.